Fables of scarcity in IP - Said, Zahr K. (Frontiers in Research Metrics and Analytics, 2023)
In this chapter, I bring textual analysis to bear on artificial scarcity and explore how literary and legal storytelling engages in scarcity mongering. I identify three particular narrative strategies calculated to compel a conclusion in favor of propertization: the spectacle of need, the diversionary tactic, and the rallying cry. First, I unpack the spectacle of need and its diversionary aspects through several literary accounts of scarcity and starvation. I juxtapose Franz Kafka’s “A Hunger Artist,” a story explicitly centered on a wasting body, with J.M. Coetzee’s The Life and Times of Michael K. Second, to explore how scarcity fables offer diversionary tactics that redirect attention away from actual scarcity, I consider NFTs, or non-fungible tokens. NFTs reflect the arbitrary value scarcity can produce, especially when artificially generated. Yet NFTs offer a spectacle of need that distracts from actual scarcity, riding a wave of expansionist property logic that suggests that more ownership is the answer. Third, to consider the scarcity fable’s propertarian rallying cry, I offer an extended close reading of a copyright dispute, Leonard v. Stemtech, involving a pair of microscopic stem cell photographs deemed so scarce they were valued at 100 times their past licensing history. Leonard illustrates how a scarcity fable may look in the context of intellectual property (“IP”).The nature of this chapter is necessarily conceptual and speculative, designed to raise questions rather than attempting conclusively to answer them. Through juxtaposition of literary accounts and one legal case study, fables of scarcity emerge as a genre whose very appearance in certain contexts ought to give scholars and policymakers pause. In copyright litigation, in which expansionist property narratives may be especially harmful to the public domain and subsequent creators, scarcity fables may be made to provide apparent support for potentially dangerous changes. Identifying scarcity fables as such when they appear in copyright cases could trigger review of the asserted scarcity and a more searching inquiry into whether the proposed solution could worsen actual scarcity.